Assuring the Extent of Climate Change and Mitigation Strategies in Nakasongola District in Uganda: Practices and Experiences of Local Farmers (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Background: In Uganda, climate change is amongst the most substantive challenges inflicting on the wellbeing of humans in many parts of the country. In the central and south western parts of Uganda where the majority of the population rely on subsistence agriculture, climate change has adversative effects. In rural areas, low resilient capacity to shocks exacerbates the impacts of climate change such as food production catastrophe, hence resulting into food insecurity. It is upon the above experiences that this study assessed emphasis on mitigation strategies and practices of climate change among farmers Nakasongola district by using qualitative research. This research was guided by one research question, namely: what are the mitigation strategies practiced by local people to minimize the impact of climate change?Material and method: The study employed a case study design where several instrumental bound cases are examined. We utilized multiple data collection methods to explore perceptions of climate change. Qualitative data for this study was generated from 15 selected households through focus group discussions, key informant interviews, and in-depth interviews. Data were collected using semi-structured interviews from fifteen purposefully selected local farmers from selected sub counties.Results: The findings of this study revealed that, farmers were found to practice mitigation strategies such as afforestation, agroforestry and agricultural intensification as ways to overcome climate change.Conclusion: Local farmers have intensively initiated agricultural policies that strive to protect the environment and such mitigation strategies are meant to enhance the capability of smallholder’s farmers to deal with the persistent effects of climate change